Process simulation as a decision support tool for biopharmaceutical process development in a South African context - Collair, Wesley (Centre for Bioprocess Engineering Research, 2021)
In 2010 the incidence of neo-natal Group B Streptococcus (GBS) disease in South Africa was 3 per 1000 live births, more than twice the global average of 1.21 per 1000 live births. A recent life cycle impact assessment showed that a new vaccine against GBS disease in South Africa could have a potential value of $ 2 million - $ 4 million /kg (R 25 million - R 50 million /kg), as an attractive investment opportunity if a novel process can be successfully synthesised and licensed commercially. In the current global market new biopharmaceutical products require innovative and expedited development pathways. To achieve this, low-cost analytical tools with short turnaround times are needed to assist with process development decision making. Process simulation is one such tool which has been shown to be useful for evaluating process development decisions without the typically expensive investment required for experimental development of a new process. Three technology platforms (stainless steel, single-use, and a hybrid of both) were identified for use in a novel process to manufacture a GBS serotype III polysaccharide-protein conjugate antigen, for formulation into a vaccine against GBS disease. The three technology choices were compared and evaluated for the novel process at two fermentation scales of 20 L and 200 L, with cost of goods (COG) used as a comparison of economic performance for the six different scenarios. It was hypothesised that single use technology would yield the lower COG at both scales compared to stainless steel. Based on a literature survey, single use technology should require lower capital costs for pilot scale processes and should also have lower operating costs due to single use equipment not requiring sterilisation in place (SIP) and cleaning in place (CIP). It was further hypothesised that hybrid technology would yield the lowest COG by combining the best properties of stainless steel and single use technologies. A 3 x 2 factorial experiment design was used to structure the simulation exercise with three technologies at each of the two scales. A GBS serotype III process model was synthesised from literature sources, with fermentation stoichiometry based on an empirical material balance and fermentation kinetics fitted to a two-parameter Monod kinetic model. Equipment, consumables, and raw materials specifications were made using literature and empirical models. A base case simulation model, built for 20 L scale using stainless steel technology, was developed into the five additional scenarios. The best performing scenario in terms COG was then selected for sensitivity analysis using three parameters: fermentation titer, solid-liquid separation efficiency, and electricity dependence on diesel generation. At 20 L scale there was little difference in COG between the three technology options, with COG range across the three platforms of $ 9.7 million - $ 9.8 million /kg. At 200 L scale the best performing technology was stainless steel with a COG of $ 3.7 million /kg, which was $ 600 000 /kg less than the COG for single use of $ 4.3 million/kg. The difference was due to a higher cost of consumables for single use technology, and negligible differences in capital costs for single use over stainless steel. The effect of SIP and CIP costs on operating cost for stainless steel technology was found to be small compared to the greater consumables cost for single use. The 200 L stainless steel process was found to be sensitive to fermentation titer, with an increase in titer to 600 mg/L resulting in the lowest COG of $ 2.2 million /kg. The process was found to be least sensitive to electricity dependence on diesel, with only a $ 60 000 /kg increase in COG when 75% of electricity was derived by diesel generator. The hypothesis was disproved, with single use technology having the higher COG at both 20 L and 200 L scales compared to stainless steel technology. Hybrid technology did not yield the lowest COG either, instead resulting in a COG somewhere between stainless steel and single use. Stainless steel technology outperformed single use and hybrid technologies in COG at both scales, contrary to both parts of the hypothesis. A process to make a GBS vaccine could be profitable at scales of 200 L and above using stainless steel technology. Process simulation modelling was effective for evaluating process technology options without performing costly physical experiments. The simulation exercise provided valuable information on the economic impact of process development decisions as well as context specific information for the South African context. This methodology is therefore recommended for commercial biopharmaceutical process development, particularly for evaluating techno-economic scenarios in different decision pathways during the development process.